Once-daily fluticasone furoate/vilanterol 100/25 mcg versus twice daily combination therapies in COPD – mixed treatment comparisons of clinical efficacy - Stynes, Gillian (Respir Res, 2015)
BACKGROUND: Fluticasone furoate (FF)/vilanterol (VI) 100/25 mcg is a once-daily inhaled corticosteroid (ICS)/long-acting beta(2) agonist (LABA) treatment approved in the United States, Canada and Europe for the long-term maintenance therapy of COPD. We report data from mixed treatment comparisons (MTC) of once-daily FF/VI against established twice-daily ICS/LABA combination therapies on clinical efficacy outcomes. METHODS: Data from 33 parallel-group randomised controlled trials (RCTs) of ICS/LABAs, of ≥8 weeks’ duration in patients ≥12 years of age with COPD, identified by systematic review, were analysed using covariate-adjusted Bayesian hierarchical models for three efficacy outcomes. Lung function, assessed by change from baseline in forced expiratory volume in one second (FEV(1)), was the outcome of primary interest (n = 28 studies). Secondary objectives were assessment of annual rate of moderate/severe exacerbations (n = 15) and patient-reported health status, measured by change from baseline in St George’s Respiratory Questionnaire (SGRQ) Total score (n = 20). Overall, 25 different treatments were included in the MTC; we report findings, including probabilities of non-inferiority, for comparisons of once-daily FF/VI 100/25 mcg with twice-daily fluticasone propionate (FP)/salmeterol (SAL) 500/50 mcg and budesonide (BUD)/formoterol (FORM) 400/12 mcg. RESULTS: For FEV(1), FF/VI 100/25 mcg demonstrated >99% probability of non-inferiority to FP/SAL 500/50 mcg and BUD/FORM 400/12 mcg using a 50 mL margin. For annual rate of moderate/severe exacerbations, FF/VI 100/25 mcg demonstrated 73% and 77% probability of non-inferiority to FP/SAL 500/50 mcg and BUD/FORM 400/12 mcg, respectively, using a 10% rate ratio margin. For SGRQ Total score, the corresponding probabilities of non-inferiority were 99% and 98%, respectively, on a 2-unit margin. Significant covariate effects were identified: increased age was associated with deterioration in FEV(1) and reduced exacerbation frequency; shorter study duration was associated with reduced exacerbation frequency. CONCLUSIONS: FF/VI 100/25 mcg was comparable with corresponding doses of FP/SAL and BUD/FORM on lung function and health status outcomes. Non-inferiority on moderate/severe exacerbation rate was not demonstrated to the same degree of confidence, though observed rates were similar. Model limitations include a weak treatment network for the exacerbation analysis and variability across the included studies. Our data support previous RCT findings suggesting that the efficacy of FF/VI 100/25 mcg on lung function and health status in COPD is comparable with twice-daily ICS/LABAs. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12931-015-0184-8) contains supplementary material, which is available to authorized users.